The Influence of Earnings Per Share (EPS), Price Earnings Ratio (PER), Price to Book Value (PBV), And Debt Equity Ratio (DER) On The Stock Return - Muh Ferial Ferniawan; Andi Kusumawati; Afdal Madein (Accounting Department, Faculty of Economics and Business, Universitas Hasanuddin, 2024)
The business community continues to be interested in investing in the capital market in light of the increasing number of investors on the IDX. Investors will be interested in the required future rate of return (return) in relation to the company's risk. This research aims to examine and analyze the effect of Earnings Per Share (EPS), Price Earninsg Ratio (PER), Price to Book Value (PBV), Debt Equity Ratio (DER) on the Stock Return. Data collection was obtained from the annual financial statements of manufacturing companies listed on the IDX for the period 2019 - 2021 totaling 20 companies, using purposive sampling method. The data analysis method uses a special application of multiple linear regression analysis with a quantitative approach. The results showed the effect of: Earnings Per Share (EPS), Price Earnings Ratio (PER) and Debt Equity Ratio (DER) have a positive and significant effect on stock returns of manufacturing companies listed on the IDX for the period 2019 - 2021. Price To Book Value (PBV) has a positive and insignificant effect on the stock returns of manufacturing companies listed on the IDX for the 2019-2021 period.